28PAccuracy of core biopsy in predicting pathologic complete response in the breast in patients with complete/near complete clinical and radiological response (Complete Responders in the Breast – CRBr): A feasibility study. (24th November 2019) - Hariharan, N; Rao, T S; Rajappa, S; Naidu, C C K; Raju, K V V N; Koppula, V; Sudhir, R; Murthy, S; Kodandapani, S; Fonseca, D
Abstract: Background: With the advent of taxanes and targeted agents in neoadjuvant chemotherapy (NACT) for breast cancer, the rates of pathologic complete response (pCR) have been steadily increasing. One of the roles of surgery in these women is to serve the purpose of a biopsy to confirm or negate a pCR. Methods: We conducted a prospective validation study. Women who had undergone a titanium clip placement followed by neoadjuvant chemotherapy (NACT), and achieved a complete/near complete clinical and radiological response were included. Eligible women underwent an MRI of the breast followed by a US guided core biopsy (CNB) of the tumour bed. The CNB was compared with the final histopathology report after definitive surgery. Results: 65 patients were recruited in this study, of whom 75% had T1/2 tumours and 39 women had hormone negative tumours. The overall rate of pCR in the breast (BrpCR) was 42%. Among women with BrpCR, only one patient had residual disease in the axilla (macrometastasis). The mean number of CNB of the tumour bed after NACT was 4. The accuracy of CNB in predicting BrpCR was 69%, with a false negative rate (FNR) of 14.8%. In a pre-planned sub-group analysis of hormone negative tumours, the FNR was 9.5%. No untoward side effects were observed in any of the patients. Conclusions: Ultrasound guided CNB of the tumor bed was useful in predicting BrpCR, especially in hormone negative tumours, with an FNR of 9.5%. Increasing the number of cores in the biopsy or changing the imaging modality could help in improving the accuracy of this method. Clinical trial identification: CTRI/2018/01/011122. Legal entity responsible for the study: The authors. Funding: Hyderabad Cancer Foundation. Disclosure: All authors have declared no conflicts of interest.